2020
DOI: 10.1021/acs.orglett.0c02961
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of l-glycero- and d-glycero-d-manno-Heptose Building Blocks for Stereoselective Assembly of the Lipopolysaccharide Core Trisaccharide of Vibrio parahemolyticus O2

Abstract: Synthesis of bacterial cell surface l-glycero-d-manno-heptose (l,d-Hep)- and d-glycero-d-manno-heptose (d,d-Hep)-containing higher carbon sugars is a challenging task. Here, we report a convenient and efficient approach for the synthesis of the l,d-Hep and d,d-Hep building blocks. Using l-lyxose and d-ribose as starting materials, this approach features diastereoselective Mukaiyama-type aldol reactions as the key steps. On the basis of the synthetic l,d-Hep and d,d-Hep building blocks, we achieved the first st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…However, an efficient strategy for their synthesis was still required. For this purpose, Wang et al 134 in 2020 reported the total synthesis of LPS core trisaccharide 1 of V. parahemolyticus O2 by utilizing the Mukaiyama aldol reaction as one of the main steps. In order to achieve the synthesis of the l , d -Hep subunit, they reacted l -lyxose 274 via several steps to obtain chiral aldehyde 275 , which was further subjected to react with silyl enol ether 276 by the Mukaiyama aldol reaction in the presence of MgBr 2 ·OEt 2 , DCM and toluene.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…However, an efficient strategy for their synthesis was still required. For this purpose, Wang et al 134 in 2020 reported the total synthesis of LPS core trisaccharide 1 of V. parahemolyticus O2 by utilizing the Mukaiyama aldol reaction as one of the main steps. In order to achieve the synthesis of the l , d -Hep subunit, they reacted l -lyxose 274 via several steps to obtain chiral aldehyde 275 , which was further subjected to react with silyl enol ether 276 by the Mukaiyama aldol reaction in the presence of MgBr 2 ·OEt 2 , DCM and toluene.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…In gram-negative bacteria, some rare monosaccharides such as L-glycero-D-manno-heptose and D-glycero-D-manno-heptose along with Kdo are usually found in the inner core region of the lipopolysaccharides, and occasionally they are also present as a part of the outer core and O-antigens. As integral part of the LPS, these monosaccharides have significant role in host-bacterium interactions, therefore, they can be used for the inhibition studies of bacterial cell wall polysaccharide synthesis and stimulation of the host immune system ( 21 ).…”
Section: Types Of Microbial Polysaccharides and Their Applicationsmentioning
confidence: 99%
“…Furthermore, l - glycero - d - manno -heptose was also prepared by de novo synthesis based on Mukaiyama-type aldol reaction . Recently, Yang and co-workers reported an efficient approach for the synthesis of d - glycero - d - manno -heptose and l - glycero - d - manno -heptose via Mukaiyama-type aldol reactions using d -ribose and l -lyxose as starting materials, respectively …”
Section: Introductionmentioning
confidence: 99%